Metacognitive Competences and Implicit Theories of Intelligence in Relation with School Achievement - Vechiu Adina-Petronela; Popa Nicoleta Laura (Sciendo, 2021)
This study aims to explore the relation between metacognitive competences, implicit theories of intelligence and school achievement among lower secondary students. The group of participants included 120 students from Iași County, with different socio-economic backgrounds. Participants completed two measures, Metacognitive Awareness Inventory (Schraw & Dennison, 1994) and Implicit Theories of Intelligence Questionnaire (Dweck, 2000). School achievement was defined as annual average grades, and family socio-economic background was self-reported. Students from socio-economic disadvantaged families scored lower for metacognitive competence, and self-reported fixed mindset beliefs, in contrast with students with favourable socio-economic family background. Therewith, metacognitive competences and implicit theories of intelligence are significant predictors of school achievement.